+0  
 
0
33
1
avatar

x^2 + bx + b + 3 = 0 has roots of the form x = (-b +/- sqrt(7))/2, where b > 0.  Find b.

 Nov 17, 2021
 #1
avatar+579 
+1

              \(b^2 - 4ac = 7\)

\(b^2 - 4(1)(b + 3) = 7\) 
       \(b^2 - 4b - 12 = 7\)
       \(b^2 - 4b - 19 = 0\) 
                            \(b = {-(-4) \pm \sqrt{(-4)^2-4(1)(-19)} \over 2(1)}\) 

                            \(b = {4 \pm \sqrt{16+ 76} \over 2}\)

                            \(b = {4 \pm 2\sqrt{23} \over 2}\)

                            \(b = 2\pm\sqrt{23}\)

 

                            \(b>0 \)

                        \(\therefore b = 2 + \sqrt{23}\)

.
 Nov 17, 2021

34 Online Users

avatar
avatar